Suitability of botanical extracts as components of complex mixtures used in herbal tea infusions—challenges and opportunities - Brendler, T.; Brinckmann, J. A.; Daoust, M.; He, H.; Masé, G.; Steffan, K.; Williams, M. (Frontiers in Pharmacology, 2022)
Herbal tea is a mainstay dosage form in practically all systems of traditional medicine and widely used in modern alternative and complementary medicine. Incorporating botanical extracts into herbal tea formulations is of vital interest to manufacturers as it allows for the use of herbal ingredients that would otherwise not be suitable for the dosage form, for instance of dosing requirements, solubility in water, sensory constraints etc. Furthermore, reducing the amount of ingredients in a formula increases compliance with dosing recommendations and thus therapeutic benefit. However, formulating with botanical extracts comes with challenges, ranging from sourcing ingredients of appropriate quality, developing suitable methods for quality control with combinations of (herbal) ingredients, processing constraints such as hygroscopicity, solubility, dispersibility, homogeneity of distribution, and packaging machinability, all the way to stability required for hot-water infusion. We report on experiences with overcoming such challenges in a set of examples and provide guidance to the extract industry on how to tap into the bagged tea sector with better suited or tailor-made solutions for the formulator.